Implementation of holistic PLP through vertical garden development and library digitalization as an effort to realize a green and digitally literate school - Asep Yudianto; Tubagus Habibi; Mohamad Rizky Al Hakim; Laila Munawaroh; Edo Dwi Cahyo (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The Holistic School Field Introduction Program (Program Pengenalan Lapangan Persekolahan/PLP Holistik) is a collaborative initiative between higher education institutions and partner schools aimed at integrating educational theory, field practice, and school environment empowerment. This holistic approach aligns with previous studies emphasizing contextual learning, digital literacy, and environmental-based education in primary schools. This study aims to describe the implementation and impact of the Holistic PLP through environmental development and school digital transformation projects. Methods: This study employed a qualitative descriptive approach based on field practice, with data collected through observation, documentation, and participatory evaluation involving the school community. The program was implemented at SDN Rawu through stages of initial observation, project planning, implementation, maintenance, and evaluation, grounded in contextual learning and sustainable education theories. Findings: The results indicate that the recycled-material-based vertical garden was successfully developed and utilized as a contextual learning medium, while the digital library system based on SLiMS Bulian 9.0 improved book collection management efficiency by up to 60% and enhanced teachers’ and students’ digital literacy. These findings demonstrate that integrating contextual learning theory with technology-based practices positively impacts the learning environment without significant adverse effects. Conclusion: The Holistic PLP program effectively enhances school environmental quality, student teacher competencies, and the sustainable use of educational technology. Novelty/Originality of this article: The novelty of this study lies in the integration of environmentally friendly projects and digital library development within a single Holistic PLP framework at the primary school level, an approach that has been rarely explored in previous PLP implementations.